The Influence of Promotion, Procedures, and Margin on Sharia Mortgage Decisions - Agustina, Dewanty Anggie (Kunuz: Journal of Islamic Banking and Finance, 2024)
This study examines the influence of promotion, credit procedures, and margins on customer decisions to apply for Sharia-compliant mortgage loans (KPR) at Bank Syariah Indonesia in Samarinda City. Utilizing a quantitative approach, data were collected through questionnaires from 101 respondents selected using purposive sampling. The respondents included KPR customers from four branches: BSI KC Samarinda Antasari, BSI KCP Samarinda Bung Tomo, BSI KCP Samarinda Juanda, and BSI KCP Samarinda Pahlawan, covering the period of 2021–2023. Data analysis was conducted using multiple regression analysis through SPSS software. The findings reveal that promotion and credit procedures significantly and positively influence customer decisions, whereas margin does not have a significant effect. Simultaneously, promotion, credit procedures, and margin collectively have a significant positive effect on customer decisions. These findings emphasize the importance of promotional strategies and simplified credit procedures to enhance customer engagement in Sharia banking products.